ATP-dependent G-quadruplex unfolding by Bloom helicase exhibits low processivity - Budhathoki, Jagat B. (Nucleic Acids Res, 2015)
Various helicases and single stranded DNA (ssDNA) binding proteins unfold G-quadruplex (GQ) structures. However, the underlying mechanisms of this activity have only recently come to focus. We report kinetic studies on Bloom (BLM) helicase and human telomeric GQ interactions using single-molecule Förster resonance energy transfer (smFRET). Using partial duplex DNA (pdDNA) constructs with different 5′ ssDNA overhangs, we show that BLM localizes in the vicinity of ssDNA/double-stranded DNA (dsDNA) junction and reels in the ssDNA overhang in an ATP-dependent manner. A comparison of DNA constructs with or without GQ in the overhang shows that GQ unfolding is achieved in 50–70% of reeling attempts under physiological salt and pH conditions. The unsuccessful attempts often result in dissociation of BLM from DNA which slows down the overall BLM activity. BLM-mediated GQ unfolding is typically followed by refolding of the GQ, a pattern that is repeated several times before BLM dissociates from DNA. BLM is significantly less processive compared to the highly efficient GQ destabilizer Pif1 that can repeat GQ unfolding activity hundreds of times before dissociating from DNA. Despite the variations in processivity, our studies point to possible common patterns used by different helicases in minimizing the duration of stable GQ formation.